Penggunaan Media Tanaman untuk meningkatkan kreativitas menggambar anak kelompok kelas A di TK AL MAISAROH BUNGATAN Situbondo - Witriyatun Hasanah (MOTORIC, 2023)
This study aims to (1) describe and analyze the application of plant media in increasing the creativity of drawing in class A children in TK Al Maisaroh Bungatan Situbondo. (2) Describing and analyzing the improvement of children's drawing creativity with plant media in class A children at Al Maisaroh Bungatan Kindergarten Situbondo. The method used is class action. The subjects in this study were Class A children at Al Maisaroh Kindergarten, which consisted of 10 children aged 4 to 5 years consisting of 6 boys and 4 girls. The results are (1) The activity of drawing plants through the class action method can increase the creativity of class A children at Al Maisaroh Bungatan Situbondo Kindergarten, the academic year 2021/2022. Children prefer to draw when the method used can make it easier for children to draw clearer and less vague shapes. (2) The increase in creativity in drawing children with plant media in class A children at Al Maisaroh Bungatan Kindergarten Situbondo can be proven from the data from learning observations in each cycle. The following is a description of each cycle: a. In this Pre-Cycle, the average achievement of drawing class A in TK Al Maisaroh Bungatan Situbondo is 42.50%, b. In Cycle I the average achievement of drawing plants increased by 22.50%, from 42.50% to 65.00%, c. In Cycle II, the average achievement of drawing plants increased by 21.88%, from 65.00% to 86.88%. The total increase that occurred from before the action (Pre-Cycle) to Cycle II was 44.38%, from 42.50% to 86.88%. with KKM 85%. Keywords: drawing creativity, plant media, class action